Household debt in different age cohorts: A multilevel study - Haq, Wajiha; Ismail, Noor Azina; Satar, Nurulhuda Mohd; Watson, Duncan (Cogent OA, 2018)
There is a need to identify household debt behaviour in different age cohorts even in countries without prominent household debt problems so that the measures for vulnerable groups can be made. Authors used multilevel mixed effect analysis to test the effect of age and other variables on demand of debt. A national representative survey data of HIES (2001–2013) based on stratified sampling design was used. Household debt in mature workers was higher than youth whereas debt of older people was not significantly different from other cohorts. Education and household size positively affect the demand for debt. This study contributed to existing literature by exploring the demand for debt in different age cohorts, taking into account other socio-economic variables. The design of debt products should be such that mature workers should not accumulate a high level of debt.